THE DIFFERENCES IN NUTRITIONAL STATUS OF CHILDREN BASED ON MATERNAL ANEMIA STATUS DURING PREGNANCY IN PUSKESMAS I HEALTH CENTER, SOUTH DENPASAR - Deviana Pramastya Putri; A.A.Gde Raka Kayanaya; I Ketut Kencana (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2019)
Nutritional status is a picture of the balance between nutritional intake and needs due to food consumption and use of nutrients. The reason children get poor nutrition is one of them has a low maternal hemoglobin level during pregnancy. This will interfere with fetal growth and cause prematurity and low birth weight. LBW in their lives will be more difficult to catch up with BB (body weight) or body length (PB), this condition will produce further nutritional status. The purpose of this study was to determine the differences in nutritional status of children based on maternal anemia status during pregnancy in the Work Area I of South Denpasar Health Center. The research method used was observational research with cross sectional design. The population in this study were all children aged 0-23 months who had biological mothers in the Working Area I of South Denpasar Health Center totaling 532 people. The sample in this study was part of a population of 88 people. The results showed that the anemia status of the majority of mothers were not anemic, namely 70 people (79.5%) and the remaining 18 people (20.5%) suffered anemia while the nutritional status of children was obtained as a result of 79 good children (89.8%), more nutritional status as many as 6 people (6.8%) and malnutrition status as many as 3 people (3.4%). After analyzing the Independent T-Test statistical test at a confidence level of 95% (α = 0.05) obtained p value = 0.056 so that there was no significant difference in nutritional status of children based on maternal anemia status during pregnancy in the South Denpasar Health Center I.Keywords: Status of Maternal Anemia, Child Nutritional Status